2010
DOI: 10.1038/jhg.2010.99
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in NRXN3, TFAP2B, MSRA, LYPLAL1, FTO and MC4R and their effect on visceral fat area in the Japanese population

Abstract: The predominant risk factor of metabolic syndrome is intra-abdominal fat accumulation, which is determined by waist circumference and waist-hip ratio measurements and visceral fat area (VFA) that is measured by computed tomography (CT). There is evidence that waist circumference and waist-hip ratio in the Caucasian population are associated with variations in several genes, including neurexin 3 (NRXN3), transcription factor AP-2b (TFAP2B), methionine sulfoxide reductase A (MSRA), lysophospholipase-like-1 (LYPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 21 publications
4
26
1
2
Order By: Relevance
“…[15][16][17][18][19] We confirmed that some of these SNPs are also associated with obesity and visceral fat area as determined by computed tomography in the Japanese population. [20][21][22] In this study, we investigated the association between metabolic syndrome and 33 SNPs related to obesity and the obesity-related phenotype. We found that SNPs in the fat mass and obesity associated (FTO), SCG3 and MTMR9 genes are associated with metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] We confirmed that some of these SNPs are also associated with obesity and visceral fat area as determined by computed tomography in the Japanese population. [20][21][22] In this study, we investigated the association between metabolic syndrome and 33 SNPs related to obesity and the obesity-related phenotype. We found that SNPs in the fat mass and obesity associated (FTO), SCG3 and MTMR9 genes are associated with metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Among the reported loci, we have reported that the rs1558902 and rs1421085 genotypes of the fat mass-and obesityassociated gene (FTO) were significantly associated with VFA, as well as with subcutaneous fat area (SFA) and body mass index (BMI). 11 GWAS and meta-analysis of GWAS have also identified metabolic syndrome trait-associated genetic variations, including obesity, type 2 diabetes, dyslipidemia and hypertension. 12 We have previously reported that among the single-nucleotide polymorphisms (SNPs) susceptible to obesity, [13][14][15] rs7498665 in the SH2B adaptor protein 1 (SH2B1) gene was associated with VFA, 16 and that among hypertension-susceptible SNPs, 17,18 rs1004467 in the cytochrome P450, family 17, subfamily A, polypeptide 1 (CYP17A1) gene and rs11191548 in the 5¢-nucleotidase, cytosolic II (NT5C2) gene were significantly associated with both reduced VFA and SFA in women, indicating a genetic background to central obesity.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In a previous study, we have reported that the rs1558902 and rs1421085 genotypes of the fat mass and obesity-associated gene (FTO) were significantly associated with VFA, as well as with subcutaneous fat area (SFA) and body mass index (BMI). 8 We performed a large-scale, case-control association study and found that secretogranin III (SCG3) 9 and myotubularin-related protein 9 (MTMR9) 10 conferred susceptibility to an obese phenotype in the Japanese population. Recent progress in genome-wide association studies has increased the number of known genetic susceptibility loci for obesity.…”
Section: Introductionmentioning
confidence: 99%